Influência do sistema de cultivo e manejo do solo nas propriedades físico-químicas e hídricas em cambissolo no semiárido potiguar - Oliveira, Líssia Letícia de Paiva (2016)
Inadequate management systems can promote the degradation of the physical and chemical soil quality, with environmental reflexes and productivity. In this sense, the objective of this work was to seek a direction regarding the water retention, the influence of organic matter, Ca 2+ and Mg 2+ in soil aggregation and the physical and chemical attributes of the soil due to the different agricultural practices and soil management, to identify which of these are the most sensitive in the environments distinction, having the forest preserved as a reference. But also specifically evaluate the attributes of soil, indicating which of these have provided improvements or restrictions in the evaluated environments, in a Cambisol the Settlement Project Land of Hope, located in the city of Governador Dix-sept Rosado - RN, located in the middle region of the West Potiguar and the micro-region of Apodi Chapada. The areas analyzed were preserved forest area (AMP), cajaranas orchard area (AP) consortium area corn / beans (ACMF), watermelon consortium Area / jerimum (ACMJ) and agroecological area (AA). collection of disturbed and undisturbed samples were carried out in layers from 0.00 to 0.10; .10 To .20; 0.20 to 0.30 m, benefited the Soil Analysis Laboratory Water and Plant - LASAP / DADA / UFERSA. The analysis constituted the particle size, particle density, bulk density, porosity, macro and micro porosity, field capacity, permanent wilting point, available water, water retention curve in the soil, aggregate, EC, pH, TOC , P, K, Na, Ca, Mg and TOC PST, Ca and Mg added within each class. The greatest amount of TOC was observed in the AP, due probably to supply litter found in the location associated with the excrement of animals (goats, cattle, horses and donkeys) in the grazing area. Regarding the texture, the soils of ACMJ had higher clay content (0.55, 0.58 and 0.63 kg kg-1) in the three layers studied and can be justified because it is a colluvial area. It was observed that the soils under conventional tillage (ACMF and ACMJ), regardless of plant cultivation, possibly promoted a greater aeration of the soil and a lower DS, as evidenced by an increase of macropores in the superficial layer. AP provided the best water retention conditions compared to the other treatments, due to the maintenance of soil cover and increase soil organic carbon. In conventional management areas ACMF and ACMJ percent aggregation , aggregate stability and mean weight diameter were reduced compared to the preserved area ( AMP) in all layers. Agricultural uses ACMF (area of corn consortium / beans) and ACMJ ( watermelon consortium of area / pumpkin ) altered the degradation of the physical attributes ( bulk density and aggregation ) and chemical (total organic carbon and Mg 2+ ) soil compared to preserved forest area (AMP)